2017
DOI: 10.13075/ijomeh.1896.00669
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and apotosis to Zebrafish (Danio rerio) embryos exposed to perfluorooctane sulfonate (PFOS) and ZnO nanoparticles

Abstract: Objectives: Perfluorooctane sulfonate (PFOS) and zinc oxide nanoparticles (ZnO-NPs) are frequently detected in the environment but few studies have assessed the joint toxicity of them. Oxidative stress and apoptosis to zebrafish (Danio rerio) embryos induced by the PFOS and ZnO-NPs were investigated in this study. Material and Methods: The embryos were exposed to the PFOS (0, 0.4, 0.8 and 1.6 mg/l), 25, 50 mg/l) and PFOS plus ZnO-NPs (0.4+12.5, 0.8+25 and 1.6+50 mg/l) mixture solutions until 96 h post-fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 51 publications
6
36
0
Order By: Relevance
“…Silver nanoparticles (AgNPs) have been shown to induce OS in human colon cancer cells through increased LPO and reduced GSH levels with the induction of mitochondria-involved apoptosis via the elevated levels of Bcl and caspase-3 proteins [34]. ZnO NPs have also proved to induce the expression of the genes attributed to ROS generation, OS damage and apoptosis such as Bax, p53, caspase-3 and caspase-9 [35]. Another study has also demonstrated that biogenic NPs (tellurium nanorods) induced necrosis or late apoptosis without altering the activity of caspase pathway [22].…”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) have been shown to induce OS in human colon cancer cells through increased LPO and reduced GSH levels with the induction of mitochondria-involved apoptosis via the elevated levels of Bcl and caspase-3 proteins [34]. ZnO NPs have also proved to induce the expression of the genes attributed to ROS generation, OS damage and apoptosis such as Bax, p53, caspase-3 and caspase-9 [35]. Another study has also demonstrated that biogenic NPs (tellurium nanorods) induced necrosis or late apoptosis without altering the activity of caspase pathway [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles can induce oxidative stress in human fibroblasts, erythrocytes, vascular endothelial cells, mesenchymal stem cells and a variety of tumour cells (Abdal Dayem et al, ). Nanoparticles have also been shown to cause oxidative stress in zebrafish embryos and in the liver of adult zebrafish (Choi et al, ; Du, Cai, Wang, & You, ; Faria et al, ; Zhao et al, ). Catalase, glutathione peroxidase (GPX) and superoxide dismutase (SOD) are detoxifying enzymes for ROS that regulate redox homeostasis (Abdal Dayem et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl2 plays an important role in the regulation of ROS generation and maintenance of the redox status (Hockenbery, Oltvai, Yin, Milliman, & Korsmeyer, ). Du et al () showed that zinc oxide nanoparticle treatment resulted in significant increases in SOD and GPX activities in zebrafish embryos. Zhao et al () also demonstrated significantly increased SOD activity in zebrafish embryos treated with zinc oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malondialdehyde (MDA), a representative lipid peroxide, is generated in cells when oxygen radical levels increase [29]. The activity of SOD2 and GPx, as well as the concentration of GSH and MDA, was used to measure the oxidative stress level in this study [30,31]. Bcl-2 is a mitochondrial membrane protein that blocks the apoptotic cell death [32].…”
Section: Introductionmentioning
confidence: 99%